Thermoelastic Cylinder Subjected to Suddenly Applied Radial Symmetric Pressure - Marjanov, M.M. (Engineering Transactions, 1986)
Stresses, temperature and oscillations of a thermoelastic cylinder suddenly cxposed to the radial symmetric pressure are analyzed in the paper. Solution of the corresponding eigenvalue problem is obtained by means of the perturbation technique, so that all the results are expressed as function of eigenvalues and eigenfunctions of the corresponding uncoupled (elastic) eigenvalue problem.